Leo Löwenthal and Herbert Marcuse: Friendship as a Redemptive Utopia - Jansen, Peter-Erwin (2025)
On October 28, 2021, Professor Jansen gave a lecture based on an English version of this text (authored by himself and Professor Engel) in the Mini Auditorium of the Faculty of Letters at the University of Costa Rica. During the social media broadcast, while the speaker read, the text translated into Spanish was projected on the screen. We present it here, with slight variations, to the reading public.